2016
DOI: 10.3389/fbioe.2016.00075
|View full text |Cite
|
Sign up to set email alerts
|

Subfailure Overstretch Injury Leads to Reversible Functional Impairment and Purinergic P2X7 Receptor Activation in Intact Vascular Tissue

Abstract: Vascular stretch injury is associated with blunt trauma, vascular surgical procedures, and harvest of human saphenous vein for use in vascular bypass grafting. A model of subfailure overstretch in rat abdominal aorta was developed to characterize surgical vascular stretch injury. Longitudinal stretch of rat aorta was characterized ex vivo. Stretch to the haptic endpoint, where the tissues would no longer lengthen, occurred at twice the resting length. The stress produced at this length was greater than physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…P2X7R antagonism restores stretch-induced loss of contractile functions and prevents eATP release in RA We previously showed that P2X7R is activated by subfailure overstretch in the RA model [15]. Immunohistochemical staining of RA showed that P2X7R is expressed in the medial and endothelial layers of RA (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…P2X7R antagonism restores stretch-induced loss of contractile functions and prevents eATP release in RA We previously showed that P2X7R is activated by subfailure overstretch in the RA model [15]. Immunohistochemical staining of RA showed that P2X7R is expressed in the medial and endothelial layers of RA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Subfailure overstretch injury impairs functional responses and causes release of extracellular ATP in RA To examine mechanical injury to vein graft under controlled conditions, we previously developed a subfailure overstretch (longitudinal) injury model using isolated rat abdominal aorta (RA) [15]. Subfailure overstretch injury impaired the contractile response of isolated RA to depolarizing KCl (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations